A Study on User's Perception towards Learner-generated Comics - Azman, Farah Nadia; Zaibon, Syamsul Bahrin; Shiratuddin, Norshuhada (International Review of Management and Marketing, 2016)
Similar to computer games which are formerly intended copiously for amusement purpose, the adoption of comics in education has also been a subject of great interest among the scientific community. An abundance of research have been conducted on the cognitive and affective effects of comics in the past. However, few of these studies aimed at extending our understanding towards learners' perception, interest, and prior knowledge in educational generated comics. Therefore, this paper discusses student's motivation, obstacles, and requirements for the implementation and design of learner-generated comics. The findings of this study contribute to the literature by providing useful information for educators and instructional designers in formulating strategies for unlocking the potential of comics within classroom environment. Keywords: Comics, Educational Comic, Instructional Design, Learner-Generated Content JEL Classifications: C610, C623, I23